2022
DOI: 10.1002/anie.202212278
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Heterogeneous Catalysis with Strong Metal–Support Interactions: Characterization, Theory and Manipulation

Abstract: Strong metal-support interactions (SMSI) represent a classic yet fast-growing area in catalysis research. The SMSI phenomenon results in the encapsulation and stabilization of metal nanoparticles (NPs) with the support material that significantly impacts the catalytic performance through regulation of the interfacial interactions. Engineering SMSI provides a promising approach to steer catalytic performance in various chemical processes, which serves as an effective tool to tackle energy and environmental chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 132 publications
1
103
0
3
Order By: Relevance
“…Various strategies have been developed to create defect sites, , metal–oxide interfaces, , grain boundaries, and hierarchical pore structures. , Among them, metal–oxide interfaces are of particular importance since they can induce electronic metal–support interaction (EMSI) by causing charge redistribution at the interface. This can modulate the unoccupied d states of noble metal sites and significantly improve reactant adsorption and activation, thereby enhancing catalytic performance. …”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been developed to create defect sites, , metal–oxide interfaces, , grain boundaries, and hierarchical pore structures. , Among them, metal–oxide interfaces are of particular importance since they can induce electronic metal–support interaction (EMSI) by causing charge redistribution at the interface. This can modulate the unoccupied d states of noble metal sites and significantly improve reactant adsorption and activation, thereby enhancing catalytic performance. …”
Section: Introductionmentioning
confidence: 99%
“…A nonnegligible portion of the signals are contributed by the bulk counterparts of the supported nanoparticles. Low-energy ion scattering (LEIS), particularly high sensitivity-low energy ion scattering (HS-LEIS), enables a more precise analysis of the elemental composition of the outmost atomic layers, yet assessing the corresponding electronic characteristics remains challenging.…”
Section: Characterization and Identification Of Smsimentioning
confidence: 99%
“…Nishihata et al discovered that Pd in LaFe 0.57 Co 0.38 Pd 0.05 O 3 reversibly moves into (as lattice cations) and out of (as supported particles) the perovskite substrates at oxidative and reductive atmospheres, respectively . The driving force behind this is minimization of surface energies involving enthalpy changes, while recent studies have indicated that the entropy aspect also plays a significant role. The emergence of high-entropy materials directs a fundamentally distinct route to manipulating the dispersion of the supported active species.…”
Section: New Architectures For Smsimentioning
confidence: 99%
“…For example, supported metal nanoparticles can be dispersed into isolated metal atoms through an electronic or covalent metal−support interaction and then possess high stability and activity. 1,2 Migration of support species onto the surface of metal nanoparticles and formation of ultrathin encapsulation overlayers, known as the strong metal−support interaction, 3,4 can strongly influence catalytic reactions over metal/oxide catalysts. 5,6 For supported oxide catalysts, a strong oxide− support interaction effectively modulates their interfacial atomic and electronic structures and forms interfacial active centers.…”
mentioning
confidence: 99%
“…For supported metal or oxide nanocatalysts, the interfacial interaction between catalyst and support plays an important role in their structures and catalytic performance. For example, supported metal nanoparticles can be dispersed into isolated metal atoms through an electronic or covalent metal–support interaction and then possess high stability and activity. , Migration of support species onto the surface of metal nanoparticles and formation of ultrathin encapsulation overlayers, known as the strong metal–support interaction, , can strongly influence catalytic reactions over metal/oxide catalysts. , For supported oxide catalysts, a strong oxide–support interaction effectively modulates their interfacial atomic and electronic structures and forms interfacial active centers. , Oxide nanolayers grown on metal surfaces are usually metastable but highly active, which has been discussed in terms of the interface confinement effect in the oxide/metal inverse catalysts …”
mentioning
confidence: 99%